1996
DOI: 10.3109/09638289609166038
|View full text |Cite
|
Sign up to set email alerts
|

Planning a health education programme for the elderly visually impaired person –- a focus group study

Abstract: Focus group methodology was used with the aim of learning how persons with the diagnosis of age-related macular degeneration perceived and described their disease, and how the disease had changed their activities of daily living (ADL). This information is seen as critical in designing a health education programme. The focus group participants described problems in performing ADL. Factors contributing to the ADL problems were categorized as functional limitations in, and feelings about performing, ADL. The part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 21 publications
1
54
0
1
Order By: Relevance
“…A significantly higher percentage of the participants with ARMD also used personal assistance for mobility. This also confirms earlier findings where outdoor mobility was one of the activities with which persons with ARMD have major difficulty [2]. We suggest there is a need for assistive mobility devices for persons with ARMD to remain independent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A significantly higher percentage of the participants with ARMD also used personal assistance for mobility. This also confirms earlier findings where outdoor mobility was one of the activities with which persons with ARMD have major difficulty [2]. We suggest there is a need for assistive mobility devices for persons with ARMD to remain independent.…”
Section: Discussionsupporting
confidence: 92%
“…Being independent in ADL does not mean, however, that the device users did not experience difficulties in performing ADL. In an earlier study of ARMD it was found that a first sign of ADL disability was a feeling of insecurity in performing ADL [2]. The use of assistive devices was found to be an important strategy for ensuring independence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the preliminary stages the focus-group study gave an understanding of the problems in daily occupations faced by people who suffer from AMD, as well as important indications and ideas for further planning and evaluation of the health education programme (11). To further develop and improve the programme and to maximize the success, focus-group methodology was also used in a later stage as a tool for process evaluation (12).…”
Section: Introductionmentioning
confidence: 99%
“…performance of daily activities is the result of P-E-A transactions. 5,6 More specifically, the personal component can be expressed in terms of functional capacity, 2 motivation, coping resources 7 and adaptive strategies, 8 and the environmental component as e.g. physical environmental demands in housing.…”
Section: Introductionmentioning
confidence: 99%